1969
DOI: 10.1002/ijch.196900014
|View full text |Cite
|
Sign up to set email alerts
|

Fulvenes and Thermochromic Ethylenes, Part 53 The Fine Structure of 2‐Arylmethylene‐1,3‐Indandiones; their Dipole Moments and Electronic Spectra

Abstract: The molar refractions (polarizabilities) and dipole moments of fourteen 2‐arylmethylene‐1,3‐indandiones (I) and the electronic absorption spectra of twenty‐one representatives of this series have been measured. From these data certain features of the fine structure of the compounds have been deduced; inter alia, the carbonyl groups in I are bent away from the benzene ring of the indane moiety, and the 4‐dimethylaminophenyl compound II exists to a significant extent in the zwitterionic form IIA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1969
1969
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…2-Ferrocenylmethylene-1,3-indandione has a moment of 2.03 D,176 to be compared to 1.17 for 2-benzylidene-1,3-indandione. 177 In agreement with this the two carbonyl stretching frequencies show a significant shift (Ao, = -12 and Ai>2 = -13 cm-1 in CH2CI2; Ap, = -7 and Aj>2 = -8 cm-1 in CCI4) when compared with 2-benzylidene-1,3-indandione. This evidence led to the suggestion that in the former compound there is a contribution of extreme polar forms having negative charge on the oxygen.…”
Section: A Iron and Chromium Complexessupporting
confidence: 72%
“…2-Ferrocenylmethylene-1,3-indandione has a moment of 2.03 D,176 to be compared to 1.17 for 2-benzylidene-1,3-indandione. 177 In agreement with this the two carbonyl stretching frequencies show a significant shift (Ao, = -12 and Ai>2 = -13 cm-1 in CH2CI2; Ap, = -7 and Aj>2 = -8 cm-1 in CCI4) when compared with 2-benzylidene-1,3-indandione. This evidence led to the suggestion that in the former compound there is a contribution of extreme polar forms having negative charge on the oxygen.…”
Section: A Iron and Chromium Complexessupporting
confidence: 72%
“…Absorption spectra of DMABI films of different thickness ( d ), a powder of crystal of α-modification (the optical density of the bulk α-crystals was too high to be measured), and the DMABI solution in n -heptane (10 -5 mol/L) are shown in Figure . The absorption spectra of DMABI solutions were analyzed in previous publications. , It has been shown that the spectrum can be divided into two groups of bands which are of different origin. The bands in the high-energy spectral region (maximum at 5.03 eV) correspond to the absorption of the indandione fragment of the molecule .…”
Section: Resultsmentioning
confidence: 99%
“…Owing to different electron donor and acceptor properties of fragments, an asymmetric charge distribution takes place. The dipolar character , of the DMABI molecule and the excellent photoconductivity 2 ( i photo / i dark = 10 4 −10 5 ) of DMABI crystals have already been discussed in pioneering studies almost 25 year ago. Similar to many carbocyclic and heterocyclic organic compounds, DMABI crystals exhibit well-expressed polymorphism.…”
Section: Introductionmentioning
confidence: 97%